2005
DOI: 10.1111/j.1439-0507.2004.01057.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of phospholipase and proteinase activity in Candida albicans and C. dubliniensis

Abstract: Although the production of virulence enzymes by Candida albicans has been extensively explored, little attention has been given to the virulence factors of C. dubliniensis. In the present study, an attempt was made to investigate phospholipase activity (Pz value) and secretory aspartyl proteinase production of C. dubliniensis and compare it with C. albicans. None of the 87 C. dubliniensis isolates tested, produced phosholipases whereas, in contrast all the 52 (100%) C. albicans isolates tested demonstrated var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
1
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 33 publications
4
31
1
4
Order By: Relevance
“…Furthermore, P. dioscoridis extract decreased the ability of Candida to produce these enzymes, which was in agreement with the results reported by Ibrahim et al [44]. The virulence of Candida species is attributed not to a single factor but to a combination of several factors [45], including proteinase, phospholipase [46], and hemolysin production [47]. These data suggest that the capacity of C. albicans to produce these enzymes must have a role in its pathogenic potential.…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, P. dioscoridis extract decreased the ability of Candida to produce these enzymes, which was in agreement with the results reported by Ibrahim et al [44]. The virulence of Candida species is attributed not to a single factor but to a combination of several factors [45], including proteinase, phospholipase [46], and hemolysin production [47]. These data suggest that the capacity of C. albicans to produce these enzymes must have a role in its pathogenic potential.…”
Section: Discussionsupporting
confidence: 82%
“…There are several studies related to virulence factors of Candida species. According to some authors, secreted aspartic proteinases and phospholipase are produced at high rates in C. albicans, while non-albicans Candida species usually present low rates of these enzymes 10,11,14,17 . KOGA-ITO et al 16 showed an increased proteinase and phospholipase production among the C. albicans strains isolated from oral candidiasis patients when compared to those ones isolated from control individuals.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have suggested that the absence or decreased expression of these hydrolytic enzymes may lead to reduced virulence of Candida species, and these enzymes have been shown to contribute to C. albicans morphological transition, colonization, cytotoxicity, and penetration of the host (67,68). Evidence from one study strongly suggested that the invasive C. albicans strains exhibited significantly stronger extracellular phospholipase activity than the noninvasive strains (69).…”
Section: Potential Drug Targets In C Albicansmentioning
confidence: 97%
“…Moreover, the lipase inhibitor ebelactone B and the proteinase inhibitor pepstatin A were also reported to reduce the damage to human tissues caused by Candida species (74,75). A greater effort in understanding the roles of the hydrolytic enzymes in fungal pathogens is needed, although it is clear that hydrolytic enzymes play an important role in the pathogenicity of several Candida species (67,68).…”
Section: Potential Drug Targets In C Albicansmentioning
confidence: 99%